Value and Cultural Voice in Australian Aboriginal Textiles. (1st October 2020) - Ruben, Bobbie; Naylor, Stephen; McDonald, Malcolm
Abstract: Screen-printed textiles from remote Australian Aboriginal communities are a widely acclaimed and celebrated form of cultural expression. They bring substantial benefits to artists and their communities. This paper describes research that examines ways in which textiles are understood and valued in the context of their collaborative intercultural development whilst also examining "cloth" as a unique creative medium for conveying cultural narratives. Australia's colonial past may cast subsequent intercultural collaboration in a negative light. However, this paper proposes the hypotheses that non-Indigenous collaborative contribution to textile creation does not diminish the power of this work for artists; nor does it lessen the cultural meaning and value of the ancestral stories portrayed. An additional inter-related hypothesis holds that cloth carries a cultural voice in a way that other forms of cultural production cannot. Yet the journey taken by these textiles is precarious. "Industry" can undervalue the cultural narratives and potentially expose Aboriginal screen-printed textiles to commercial misuse. A proposed qualitative research investigation will test the hypotheses, with a focus on how textiles are understood and valued by artists who create the work and by key participants along their journey.